The impact of globalisation towards bank performance in Malaysia - Mugeshmani, Supramaniam (2018)
The purpose of this study is to shed some crucial light on the relationship between globalisation and performance of the banking system in Malaysia. This study uses a range of bank-characteristic determinants (internal factors), macroeconomic determinants (external factors) and three different dimensions of globalisation including economic globalisation, social globalisation and political globalisation to explain local commercial bank performance in Malaysia. This study uses regression analysis based on the secondary data for local commercial banks in Malaysia. The period for this secondary data is 10 years which is from the year 2008 till 2017. This study indicates that there is strong evidence stating both economic and politic globalisation have negatively significant effects on the bank performance in Malaysia. Meanwhile, social globalisation shows an insignificant result on this. As for bank characteristics variables, credit risk shows a negatively significant result towards bank performance in Malaysia while bank size shows a positive and significant result towards bank performance in Malaysia. Sole macroeconomic variable which is GDP does not show any significant result towards the bank performance in Malaysia. Therefore, central bank of Malaysia should give some incentive training for local bankers on how to adopt new supervision and risk management. This will give the local bankers some new knowledge to handle better risk management and directly boost the bank performance. Besides that, banks should develop their credit risk management to overcome any default loans and for better financial performances. Banks in Malaysia also need to expand their businesses as larger banks gives a larger facility which directly boots the bank performance. It is also recommended for Malaysian banks to improve their forecasting of macroeconomic fluctuations in future to achieve greater efficiency levels.